Dry‐Deposited Transparent Carbon Nanotube Film as Front Electrode in Colloidal Quantum Dot Solar Cells. Issue 2 (22nd November 2016) - Zhang, Xiaoliang; Aitola, Kerttu; Hägglund, Carl; Kaskela, Antti; Johansson, Malin B.; Sveinbjörnsson, Kári; Kauppinen, Esko I.; Johansson, Erik M. J.
Abstract: Single‐walled carbon nanotubes (SWCNTs) show great potential as an alternative material for front electrodes in photovoltaic applications, especially for flexible devices. In this work, a press‐transferred transparent SWCNT film was utilized as front electrode for colloidal quantum dot solar cells (CQDSCs). The solar cells were fabricated on both glass and flexible substrates, and maximum power conversion efficiencies of 5.5 and 5.6 %, respectively, were achieved, which corresponds to 90 and 92 % of an indium‐doped tin oxide (ITO)‐based device (6.1 %). The SWCNTs are therefore a very good alternative to the ITO‐based electrodes especially for flexible solar cells. The optical electric field distribution and optical losses within the devices were simulated theoretically and the results agree with the experimental results. With the optical simulations that were performed it may also be possible to enhance the photovoltaic performance of SWCNT‐based solar cells even further by optimizing the device configuration or by using additional optical active layers, thus reducing light reflection of the device and increasing light absorption in the quantum dot layer. Abstract : Bringing the light : A press‐transferred, transparent, single‐walled carbon nanotube film is utilized as front electrode for planar colloidal quantum dot solar cells. The solar cells are fabricated on both glass and flexible substrates, and maximum power conversion efficiencies almost equal to that of an indium‐doped tin oxide‐based device can be achieved.